Prevalence of Pneumonia with Congenital Heart Disease in Children at District Dera Ismail Khan, Pakistan - Meshkat Ali Shah, Kiramat Ali, Nasir Zia, Fouzia Jameel, Jaweria Gul (Pakistan Journal of Medical & Health Sciences, 2022)
One of the more severe infections, pneumonia involves an infection of the lungs, more specifically the alveoli. It is a significant issue for public health and the main cause of sickness and mortality in children under five, particularly in underdeveloped nations. The purpose of the current study was to determine the prevalence of pneumonia with congenital heart disease (CHD) in children. In this study, there were 765 children were involved and among them, 245 children were infected with pneumonia. Among total of 360 male and 405 female children, 33.06 and 31.11%, respectively had pneumonia. 1-2 years child had severe pneumonia infection (39.80%) followed by 3-4 years (36.04%), 5-6 years (30.87%), 7-8 years (25.58%), and 9-10 years (19.81%). The highest pneumonia prevalence was seen in 1-2 years of age. Female child were highly infected with pneumonia as compared to male. Heart failure and murmurs were more prevalent in children with CHD. Factors significantly associated with pneumonia included: age below 6 months, lack of exclusive breastfeeding during the first six months, rural residence, severe acute malnutrition, not up-to-date for age immunization status, and exposure to cigarette smoke. Pneumonia was common in youngsters under the age of five. Addressing the associated factors could lower the prevalence of pneumonia because the majority of them are changeable and manageable. Keywords: Pneumonia; Congenital heart disease; Prevalence; Risk factors; Pakistan